2022
DOI: 10.1097/ec9.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

Association between duration of return of spontaneous circulation and outcomes after out-of-hospital cardiac arrest

Abstract: BackgroundReturn of spontaneous circulation (ROSC) is a core outcome element of cardiopulmonary resuscitation (CPR); however, the definition or criterion of ROSC is disputed and varies in resuscitation for out-of-hospital cardiac arrest (OHCA).MethodsThis was a retrospective study of 126 patients with OHCA who achieved ROSC between January and December 2020. The probability of survival after OHCA related to CPR and ROSC duration was analyzed using the probability density function and empirical cumulative densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…When DABI was measured quantitatively using GWR BG , it is important to note that adjusting for initial cardiac rhythm and time to ROSC nullifies the significance of this association. This is not an unexpected finding, as these factors are known predictors of outcome in post-cardiac arrest patients ( 16 , 17 ). Additionally, previous studies have suggested that GWR is misleadingly higher when CTH is performed within 6 hours of arrest and will be more accurate beyond this timeframe ( 18 ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…When DABI was measured quantitatively using GWR BG , it is important to note that adjusting for initial cardiac rhythm and time to ROSC nullifies the significance of this association. This is not an unexpected finding, as these factors are known predictors of outcome in post-cardiac arrest patients ( 16 , 17 ). Additionally, previous studies have suggested that GWR is misleadingly higher when CTH is performed within 6 hours of arrest and will be more accurate beyond this timeframe ( 18 ).…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, the body temperatures recorded in this study included axillary and ear temperatures, which are not true core body temperature measurements, and may have overestimated the number of patients in the lower body temperature group who were truly normothermic (15). Finally, some of these studies did not control for time to ROSC and other features of the cardiac arrest event that are known to contribute to mortality (11, 15–17).…”
Section: Discussionmentioning
confidence: 99%
“…The ROSC was defined as the return of blood circulation without continuous chest compressions. Sustained ROSC was defined as ROSC lasting at least 20 min (33). Cardiopulmonary resuscitation duration was recorded as the time interval from the beginning of the application of chest pressure to the termination of cardiopulmonary resuscitation (34,35).…”
Section: Definitionsmentioning
confidence: 99%